The Association between Physical Activity with Mental and Social Wellbeing among Employees of Police Guard - Mir Hamid Salehian; Zahra Ezzati Arbat (Journal of Modern Psychology, 2023)
The purpose of the current research was to determine the level of physical activity of the male employees of the police guard and also to investigate the relationships between physical activity and mental and social wellbeing in the male employees of the police guard. The current research was descriptive-correlation research. The statistical population of this research included all the male employees of police guard of Tehran in 2021. The statistical sample of the current research included 146 men who were selected through convenience sampling. Physical activity was measured using the international physical activity questionnaire (IPAQ), mental health was measured using depression anxiety and stress scale 21 (DASS-21), and social health was measured using the Keyes's social well-being questionnaire (KSWBQ). Pearson’s correlation test and structural equations were used for data analysis. Results showed that the research subjects had a body mass index with an average of 24.40 which is at an average level, but close to overweight. Also, a total of 52% of the subjects had moderate-to-vigorous physical activity. In addition, the mental and social health scores were in the average range. Moreover, physical activity had significant relationships with mental health and social health. The results of the model fit showed that the research model had a good fit. Our findings indicated the positive effects of physical activity on psycho-social health components in the male employees of police guard. These findings show that the use of strategies and interventions to improve the physical activity status of the staff of police guard is of special importance.